The Analysis of Code Mixing Used By The Employees of the Shacks Hotel at Sandy Bay Area: - Ni Luh Taman Sanji Giana Wati; Ni Nyoman Ayu Tri Hidayanti; I Made Juliarta (Focus Journal : Language Review, 2025)
The abstract of the article should be well-written and include at least the following five essential things to enable the reader to grasp what the study is about: The hotel employeees’ conversations were used in the research. Within those conversations, there were several of Code Mixing types applied. They were also applied in the daily working conversations at The Shacks Hotel. The Code Mixing types were analyzed to find out their types and functions. The research method applied in the research was qualitative method. The data were analyzed based on the Code Mixing theory proposed by Jendra (Khusaini, 2019: 120) stated that code mixing is divided into three types, namely word-form code mixing, phrase-form code mixing and clause-form code mixing. The analysis was grounded in Jendra's (Khusaini, 2019: 120) code-mixing theory, which categorizes code-mixing into three types: word-form, phrase-form, and clause-form. This research aims to understand the prevalence and purpose of these different code-mixing forms within the specific context of hotel employee interactions.